USIA PERNIKAHAN DI ERA MODERN: MENELUSURI KEBIJAKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 DAN BKKBN MELALUI PERSPEKTIF MASHLAḤAH MURSALAH - Aswad, Ajarul; Adil, Muhammad; Wijaya, Sandy (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
Indonesia as a legal country has laws and regulations that regulate various matters, including marriage issues. The marriage age is one of the regulations regulated in Law Number 16 of 2019 to overcome the occurrence of early marriage which of course has various negative impacts. Meanwhile, the National Population and Family Planning Agency (BKKBN), through the Marriage Age Maturation (PUP) program, states that the ideal age for marriage is 21 years for women and 25 years for men. This research formulates several problems, namely what are the factors behind the determination of the age of marriage according to Law Number 16 of 2019 and the National Population and Family Planning Agency (BKKBN) and what is the mashlaḥah murlah analysis of determining the age of marriage in Law Number 16 of 2019 and the Agency National Population and Family Planning (BKKBN). This research is normative juridical in nature using a library research approach. The data sources used are directly related to the research content in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis technique uses qualitative descriptive analysis techniques with deductive conclusions to determine the underlying factors and mashlaḥah murlah analysis of determining the age of marriage in Law Number 16 of 2019 and the National Population and Family Planning Agency (BKKBN). From the research results, it can be stated that the factor behind determining the marriage age is early marriage which results in various kinds of negative impacts on the couple and the prospective children who will be born. Meanwhile, the benefits of determining the marriage age include mashlaḥah dharūriyyāt, namely ḥifzh al-nafs (maintaining the soul) and ḥifzh al-nasl (maintaining offspring).